Matte polycarbonate compositions, articles, and methods of making the same

By using a combination of high aspect ratio needle filler and highly spherical polysilsesquioxane solid particles in polycarbonate, the problem of polycarbonate prone to whitening under stress is solved, achieving a low gloss matte finish and improved mechanical properties.

CN114555705BActive Publication Date: 2025-03-21TRINSEO EURO GMBH
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202080070430.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2020-09-17
Publication Date
2025-03-21
Estimated Expiration
2040-09-17

AI Technical Summary

Technical Problem

Polycarbonates are prone to stress whitening when subjected to repeated stresses, and the mechanical properties of filled polycarbonates have deterioration problems, making it difficult to achieve matte finish and improved stress whitening resistance at the same time.

Method used

A combination of high aspect ratio needle filler and highly spherical polysilsesquioxane solid particles is used as a filler for polycarbonate and is uniformly dispersed by thermoplastic forming technology to achieve a low-gloss matte finish and improved stress whitening behavior.

Benefits of technology

A low-gloss matte finish of polycarbonate products is achieved while reducing stress whitening and maintaining other required mechanical properties such as improved stress whitening resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005131522590000041
    Figure GDA0005131522590000041
  • Figure GDA0005131522590000042
    Figure GDA0005131522590000042
  • Figure GDA0005131522590000051
    Figure GDA0005131522590000051
Patent Text Reader

Abstract

A polycarbonate article formed from a thermoplastic composition is described, the thermoplastic composition comprising polycarbonate or a polycarbonate copolymer; and at least 1 weight percent of solid particles of polysilsesquioxane (PSQ) having a decomposition temperature of at least 350° C. and a needle-shaped filler, the needle-shaped filler ideally having an aspect ratio of 2 to 50. The PSQ particles are ideally spherical. The article is formed by heating the composition and shaping the heated composition, wherein the article and the filler and PSQ particles are dispersed therein, wherein the PSQ particles ideally retain their spherical morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to compositions of polycarbonates and copolymers containing polycarbonates, the compositions having a matte finish. In particular, the compositions have a matte finish while retaining desirable properties of polycarbonates, such as improved stress whitening resistance. Background Art

[0002] Polycarbonate exhibits excellent adaptability in a wide variety of applications. Many additives are known in the art for a variety of purposes, such as providing flame retardancy, enhancing impact strength, and enhancing resistance to degradation due to exposure to light and / or chemicals. While each of these additives has a beneficial effect, in many cases this benefit is only achieved at the expense of some other property. Therefore, for any given application, the additive must be carefully selected to achieve the properties required for that application.

[0003] For example, polycarbonate and copolymers containing polycarbonate have been widely used in various applications such as eyewear due to their good impact toughness and optical clarity. Unfilled polycarbonate forms a glossy surface that can be used for optical applications, but requires some fillers or the like to obtain the desired properties, such as a lower coefficient of thermal expansion and a low gloss or matte finish, for applications such as automotive parts, medical device components, electronic device components such as cell phones, and luggage. Unfortunately, while such a matte finish and aesthetics are desired in many cases, polycarbonate is subject to repeated stresses, and filled polycarbonates are known to tend to experience property degradation (see U.S. Pat. Nos. 4,243,575 and 8,871,858), which may include undesirable changes in the product finish after repeated straining (e.g., stress whitening).

[0004] It would therefore be desirable to provide a polycarbonate composition having a matte finish with improved mechanical properties, and in particular a filled polycarbonate composition having improved stress whitening behavior. Summary of the invention

[0005] The inventors have discovered that specific combinations of fillers allow for the production of low gloss filled polycarbonates without using too much total filler to obtain desired mechanical properties, such as stress whitening resistance. Illustratively, it has been discovered that a combination of high aspect ratio acicular fillers with highly spherical fillers achieves a desired low gloss (matte appearance) finish.

[0006] A first aspect of the invention is a thermoplastic composition comprising a polycarbonate or a polycarbonate copolymer and at least 1% by weight of a polysilsesquioxane solid particle having a decomposition temperature of at least 350° C. and a needle-shaped filler. In one embodiment, the filler comprises calcium. In another embodiment, the filler comprises calcium and is needle-shaped with an aspect ratio of at least 2 to 50. In another embodiment, the polysilsesquioxane solid particle has a sphericity of at least 0.9 as measured by projection of a micrograph.

[0007] A second aspect of the present invention is a method of forming an article, comprising

[0008] (i) providing a composition according to the first aspect of the present invention,

[0009] (ii) heating the composition of step (i) to a temperature sufficient to melt the polycarbonate or polycarbonate copolymer but insufficient to decompose the polysilsesquioxane solid particles, and

[0010] (iii) shaping the heated composition to form an article having dispersed therein the polysilsesquioxane solid particles and the acicular filler. In one embodiment of the method, the polysilsesquioxane solid particles retain their shape and thus have substantially the same sphericity before and after incorporation into the polycarbonate. Likewise, the acicular filler also retains its shape.

[0011] A third aspect of the present invention is an article comprising the composition of the first aspect of the present invention.

[0012] A fourth aspect of the present invention is an article comprising a polycarbonate or polycarbonate copolymer having dispersed therein a filler having an aspect ratio of at least 2 to 50 and polysilsesquioxane solid particles having a sphericity of at least 0.9 as measured by the Pentland method. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1A is a color photograph of a dart sample not according to the invention showing significant stress whitening.

[0014] Figure 1B is a color photograph of a dart sample of the present invention showing a significant improvement in stress whitening.

[0015] Figure 2 is a 500X scanning electron micrograph of a cross section of an article of the present invention.

[0016] Figure 3 is a 5000X scanning electron micrograph of a cross section of a product of the present invention. DETAILED DESCRIPTION

[0017] The composition of the present invention may be in any form useful for making polycarbonate-based articles, such as in a dry mixture, granulated or added separately when making the article, such as added separately to a melt extruder. The mixture may be prepared by any known dry mixing equipment such as a V-blender or a mill mixer, etc. When the components of the composition are granulated, they may be melt extruded into any desired shape for subsequent manufacture of the article, such as injection molding or hot or cold pressing.

[0018] The composition comprises a polycarbonate or a polycarbonate copolymer (also referred to herein as a "copolycarbonate"). A polycarbonate copolymer herein means a copolymer in which a majority (greater than 50 mol%) of the copolymer bonds are polycarbonate units, rather than ester units such as in polyester carbonates. The copolycarbonate can be a block, branched or random copolymer. Typically, the amount of carbonate units or bonds in the copolycarbonate is at least 75 mol% or even 85 mol% up to 99 mol% of the copolycarbonate. Comonomers can include any useful monomers copolymerized with polycarbonate.

[0019] As used herein, "polycarbonate" means a composition having repeating structural carbonate units of Formula 1:

[0020]

[0021] R1 can be aliphatic, aromatic or a combination thereof. In one embodiment, each R1 is an aromatic organic group, such as a group of formula (2):

[0022] -A 1 -Y 1 -A 2 - (2)

[0023] Among them A 1 and A 2 Each of is a monocyclic divalent aromatic group, and Y 1 Is one or both A 1 With A 2 In one exemplary embodiment, one atom separates A1 from A2. Illustrative, non-limiting examples of such groups are -O-, -S-, -S(O)-, -S(O2)-, -C(O)-, methylene, cyclohexylmethylene, 2-[2.2.1]-dicycloheptylene, ethylene, isopropylidene, neopentylene, cyclohexylene, cyclopentadecylene, cyclododecylene, and adamantylene. The bridging group Y 1 It can be a hydrocarbon group or a saturated hydrocarbon group such as methylene, cyclohexylene or isopropylene. Polycarbonate can be obtained by having the formula HO-R 1-0H, wherein the dihydroxy compound comprises a dihydroxy compound of formula (3):

[0024] HO-A 1 -Y 1 -A 2 -OH (3)

[0025] where Y 1 , A 1 and A 2 As mentioned above. Also included are bisphenol compounds of general formula (4):

[0026]

[0027] Where R a and R b each represents a halogen atom or a monovalent hydrocarbon group and may be the same or different, p and q are independently an integer from 0 to 4; and Xa represents one of the groups of formula (5):

[0028]

[0029] Where R c and R d Each independently represents a hydrogen atom or a monovalent linear or cyclic hydrocarbon group, and R e It is a divalent hydrocarbon group having 1 to 12 carbons.

[0030] Some illustrative examples of suitable dihydroxy compounds include the following: resorcinol, 4-bromoresorcinol, hydroquinone, 4,4'-dihydroxybiphenyl, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)diphenylmethane, bis(4-hydroxyphenyl)-1-naphthylmethane, 1,2-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2-(4-hydroxyphenyl)-2-(3-hydroxyphenyl)propane, bis(4-hydroxyphenyl)phenylmethane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 1,1-bis(hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane. -bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)isobutylene, 1,1-bis(4-hydroxyphenyl)cyclododecane, trans-2,3-bis(4-hydroxyphenyl)-2-butene, 2,2-bis(4-hydroxyphenyl)adamantane, (α,α'-bis(4-hydroxyphenyl)toluene, bis(4-hydroxyphenyl)acetonitrile, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-ethyl-4-hydroxyphenyl)propane, 2,2-bis(3-n-propyl-4-hydroxyphenyl)propane, 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane, 2,2-bis(3-sec-butyl-4-hydroxyphenyl)propane, 2.2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2,2-bis(3-allyl-4-hydroxyphenyl)propane, 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-dichloro-2,2-bis(4-hydroxyphenyl)ethylene, 1,1-dibromo-2,2-bis(4-hydroxyphenyl)ethylene, 1,1-dichloro-2,2-bis(5-phenoxy-4-hydroxyphenyl)ethylene, 4,4'- Dihydroxybenzophenone, 3,3-bis(4-hydroxyphenyl)-2-butanone, 1,6-bis(4-hydroxyphenyl)-1,6-hexanedione, ethylene glycol bis(4-hydroxyphenyl) ether, bis(4-hydroxyphenyl) ether, bis(4-hydroxyphenyl) sulfide, bis(4-hydroxyphenyl) sulfoxide, bis(4-hydroxyphenyl) sulfone, 9,9-bis(4-hydroxyphenyl) fluoride, 2,7-dihydroxypyrene, 6,6'-dihydroxy-3,3,3',3'-tetramethylspiro(bis)indane ("spirobisindane bisphenol (spirobiindane) bisphenol)"), 3,3-bis(4-hydroxyphenyl)phthalide, 2,6-dihydroxydibenzo-p-dioxin, 2,6-dihydroxythianthrene, 2,7-dihydroxyphenoxathiol, 2,7-dihydroxy-9,10-dimethylphenazine, 3,6-dihydroxydibenzofuran, 3,6-dihydroxydibenzothiophene, 2,7-dihydroxycarbazole, 3,3-bis(4-hydroxyphenyl)phthalide, 2-phenyl-3,3-bis-(4-hydroxyphenyl)phthalide (PPPBP), or any combination thereof.

[0031] Desirably, the dihydroxy compound is 1,1-bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as "bisphenol A" or "BPA"), 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)n-butane, 2,2-bis(4-hydroxy-1-methylphenyl)propane, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)-propane and 1,1-bis(4-hydroxy-tert-butylphenyl))propane or a combination thereof. Preferably, the composition comprises a polycarbonate consisting essentially of carbonate units, it being understood that trace amounts (e.g., less than 0.1 mole %) of other monomer units may be present. Particularly preferred are bisphenol A homopolycarbonates and polycarbonates that are mixed polycarbonates of bisphenol A containing, for example, 1% to up to 50 mole % of other desirable bisphenols such as 2,2-bis(3,5-dibromo-4-hydroxyphenyl)-propane. Likewise, the polycarbonate may comprise a mixture of at least two polycarbonates having different chemical properties or the same chemical properties but having different properties, such as weight average molecular weight (M). w ) or other molecular weight averages, such as number average molecular weight (M n ) or z-average molecular weight (M z ), or have different structures, such as branched and straight chains.

[0032] The polycarbonates may be prepared by any suitable method, such as methods known in the art and may include interfacial polymerization or melt polymerization as described in US Pat. No. 8,871,858, at column 7, line 37 to column 8, line 2, which is incorporated herein by reference.

[0033] Branched polycarbonates and mixtures of straight and branched polycarbonates can also be used. Branching can be achieved by adding an appropriate amount of branching agent to a dihydroxy compound (e.g., bisphenol). Usually used in an amount of about 0.5 mol % to 2 mol % of the dihydroxy compound used. The branching agent has 3 or more functional groups (e.g., 3 phenol groups). Exemplary methods for forming branched polycarbonates include those described in U.S. Patent Nos. 3,028,365, 4,529,791 and 4,677,162, the entire contents of which are incorporated herein by reference. Exemplary branching agents that can be used are tri- or polyfunctional carboxylic acid chlorides such as trimesic acid trichloride, cyanuric acid trichloride, 3,3'-,4,4'-benzophenonetetracarboxylic acid tetrachloride, 1,4,5,8-naphthalene-tetracarboxylic acid tetrachloride or pyromellitic acid tetrachloride, in an amount of, for example, about 0.01 to about 1.0 mol % (relative to the dicarboxylic acid dichloride used), or tri- or polyfunctional phenols such as phloroglucinol, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)-2-heptene, 4,4-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)- Benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, tris(4-hydroxyphenyl)-phenyl-methane, 2,2-bis[4,4-bis(4-hydroxyphenyl)cyclohexyl]-propane, 2,4-bis[1-(4-hydroxyphenyl)-1-methyl-ethyl]phenol, tetrakis(4-hydroxyphenyl)-methane, 2,6-bis(2-hydroxy-5-methyl-benzyl)-4-methyl-phenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane or tetrakis(4-[1-(4-hydroxyphenyl)-1-methylethyl]-phenoxy)-methane, which is about 0.01 to about 1.0 mol% relative to the amount of diphenol used. A phenolic branching agent can be placed in the reaction vessel together with the diphenol. An acid chloride branching agent can be introduced together with the acid chloride.

[0034] Polycarbonates are typically formed using terminating groups to achieve, for example, a desired average molecular weight or molecular weight distribution. Exemplary chain terminators for the production of polycarbonates include phenolic compounds, including phenol, p-chlorophenol, p-tert-butylphenol, 4-(1,3-dimethyl-butyl)-phenol, and 2,4,6-tribromophenol; long chain alkylphenols, such as monoalkylphenols or dialkylphenols containing a total of 8 to 20 C atoms in their alkyl substituents, exemplified by 3,5-di-tert-butylphenol, p-isooctylphenol, p-tert-octylphenol, p-dodecylphenol, 2-(3,5-dimethylheptyl)-phenol, and 4-(3,5-dimethylheptyl)-phenol. The amount of chain terminator used can be from about 0.1 mol% to about 10 mol% of the molar sum of the diphenols or dihydroxy compounds used.

[0035] Illustrative non-limiting examples of copolycarbonates include polyester carbonates and polysiloxane carbonates as described in US Pat. Nos. 3,419,634, 6,630,525 and 8,871,858. Exemplary ester-forming monomers include dicarboxylic acid halides and hydroxycarboxylic acids. Exemplary siloxane monomers include siloxane-functional bisphenols.

[0036] The polycarbonates and / or copolycarbonates may have any useful M w To form a product therefrom. w The molecular weight of the polycarbonate and / or copolycarbonate is in the range of 8,000, 12,000 or 16,000 to 200,000, 80,000 or 40,000. Unless otherwise indicated, the "molecular weight" of the polycarbonate and / or copolycarbonate referred to herein refers to the weight average molecular weight (M) determined by gel permeation chromatography (GPC) using a laser scattering technique using bisphenol A polycarbonate standards. w ), and is given in units of grams per mole (g / mole). Likewise, the melt flow rate (MFR) of the polycarbonate and / or copolycarbonate is sufficient to allow the use of the mixture to prepare the desired articles therefrom. Illustratively, useful melt flow rates are generally from about 2 or 3 to about 20 or 40 grams per 10 minutes (g / 10 minutes), as measured at 300°C and a 1.2 kg load.

[0037] The composition may contain other additives for polycarbonate. The amount of these additives present in this article is based on the weight of the polycarbonate or copolycarbonate, excluding needle-shaped fillers and polysilsesquioxane solid particles. For example, the polycarbonate or copolycarbonate used in the composition may contain one or more flame retardants commonly used in polycarbonate compositions. The flame retardant can be any flame retardant in a thermoplastic polymer known to be useful for providing flame retardant properties. Sufficient flame retardants can be used to meet the flame retardancy requirements, and their amount will not interfere with other properties of the article, making it undesirable or unfeasible. Exemplary flame retardants include halogenated compounds, carbonized salt flame retardants, phosphorus-containing compounds, oligomeric phosphates, poly (block-phosphonates) and / or poly (block-phosphonate-carbonates), see U.S. Patent No. 7,645,850, the entire contents of which are incorporated herein. Preferred oligomeric phosphates include bisphenol-A bis (diphenyl phosphate) (BAPP). Preferred flame retardant types are halogenated flame retardants. Preferred flame retardant types are brominated flame retardants. Exemplary flame retardants include brominated polycarbonates, such as tetrabromobisphenol A polycarbonate oligomers, polybrominated phenylene oxides, brominated BPA polyepoxides, brominated imides, halogenated polyacrylates, such as poly(halogenated aryl acrylates), poly(halogenated aryl methacrylates), brominated polystyrenes, such as polydibromostyrene and polytribromostyrene, decabromobiphenyl ethane, tetrabromobiphenyl, brominated α, ω-alkylene-bisphthalimides, such as N, N'-ethylene-bis-tetrabromophthalimide, oligomeric brominated carbonates, especially carbonates derived from tetrabromobisphenol A, which can be terminated with phenoxy or brominated phenoxy or brominated epoxy resins if desired. Mixtures of halogenated flame retardants can be used. Exemplary preferred halogenated flame retardants include brominated polyacrylates, brominated polystyrene and tetrabromobisphenol A polycarbonate oligomers. The flame retardant may be present in an amount of about 0.1 wt % to 30 wt % of the polycarbonate or copolycarbonate used in the composition. Preferably, the amount of the flame retardant is 1 wt % or 5 wt % to 20 wt % or 30 wt % of the polycarbonate or copolycarbonate used in the composition.

[0038] The polycarbonate or copolycarbonate may also contain a synergist, in particular an inorganic antimony compound. Such compounds are widely available or can be prepared in a known manner. Typical inorganic synergist compounds include Sb2O5, Sb2O3, sodium antimonite, etc. Antimony trioxide (Sb2O3) is particularly preferred. Based on the weight percentage of the unfilled polycarbonate or copolycarbonate composition, about 0.5 to about 15 weight percent of the synergist can be used.

[0039] The polycarbonate or copolycarbonate thereof may also contain a fluorinated anti-drip agent. Anti-drip refers to reducing the tendency of the composition to form burning drips in the event of a fire. Fluorinated polyolefins known in the art as anti-drip agents can be used in the composition of the present invention. Exemplary fluorinated polyolefins are described in EP-A 0 640 655. They are marketed by DuPont under the trade name 30N is sold. The fluorinated polyolefin can be used in pure form and in the form of a coagulated mixture of a fluorinated polyolefin emulsion and a graft polymer emulsion or a copolymer emulsion (preferably based on styrene / acrylonitrile), the fluorinated polyolefin being mixed as an emulsion with the graft polymer or copolymer emulsion and then the mixture being coagulated. The fluorinated polyolefin can also be used as a premix with a graft polymer (component B) or a copolymer (preferably based on styrene / acrylonitrile). The fluorinated polyolefin is mixed in powder form with a powder or granules of the graft polymer or copolymer, and the mixture is usually melt compounded in a conventional device such as an internal kneader, an extruder or a twin-screw extruder at a temperature of about 200 to about 330° C. The fluorinated polyolefin can also be used in the form of a masterbatch, which is prepared by emulsion polymerization of at least one monoethylenically unsaturated monomer in the presence of an aqueous dispersion of the fluorinated polyolefin. Preferred monomer components are styrene, acrylonitrile and mixtures thereof. After acid precipitation and subsequent drying, the polymer is used as a free-flowing powder. The coagulum, premix or masterbatch may have a solids content of the fluorinated polyolefin of about 5 to about 95 wt % or about 7 to about 60 wt %. Based on the weight of the composition containing the unfilled polycarbonate or its copolymer, one or more anti-drip agents may be present in an amount of about 0 wt % or more, about 0.05 wt % or more, or about 0.1 wt % or more. Based on the weight of the polycarbonate or its copolycarbonate, one or more anti-drip agents may be present in an amount of about 5 wt % or less, about 2 wt % or less, or about 1 wt % or less.

[0040] The polycarbonate or copolycarbonate may also contain at least one or more additives commonly used in polycarbonates, such as one or more lubricants, for example, mineral oil, epoxidized soybean oil, etc.; nucleating agents; antistatic agents; stabilizers; fillers other than needle-shaped fillers, which may include glass beads, mica, quartz, talc, titanium dioxide; dyes; or pigments. Such stabilizers are present to minimize ester-carbonate exchange. Such stabilizers are known in the art, for example, see USP 5,922,816; 4,532,290; 4,401,804, all of which are incorporated herein by reference, and may include certain phosphorus-containing compounds (including phosphoric acid) used alone or in combination, certain organic phosphorus compounds such as distearyl pentaerythritol diphosphate, monohydrogen or dihydrogen phosphate or monohydrogen, dihydrogen or trihydrogen phosphate compounds, phosphate compounds, and certain inorganic phosphorus compounds such as sodium dihydrogen phosphate and potassium dihydrogen phosphate, silyl phosphate and silyl phosphate derivatives.

[0041] The disclosed compositions can be produced by mixing the specific components in a known manner and melt mixing and / or melt extruding them in conventional apparatuses such as internal kneaders, extruders and twin-screw extruders at temperatures of 200° C. to 350° C. The individual components can be mixed continuously and simultaneously in a known manner at temperatures of about 23° C. (room temperature) and higher.

[0042] The composition comprises 1 wt. % of solid particles of polysilsesquioxane ("PSQ") having a decomposition temperature of at least 350°C and preferably spherical, and an acicular filler. It has been found that the combination of the acicular filler, preferably comprising calcium (e.g., wollastonite), and the PSQ particles is essential to achieving polycarbonate articles useful in aesthetic applications subjected to repeated strains (e.g., bending, etc.) having the desired or necessary low gloss (matte finish) and acceptable stress whitening properties.

[0043] It has been found that the combination of acicular fillers and preferably spherical polysilsesquioxane (PSQ) solid particles having a decomposition temperature of at least 350°C surprisingly achieves polycarbonates with an improved matte finish (low gloss) while having a low total loading of filler particles and reduced stress whitening. It should be noted that the PSQ particles do not melt when heated. When the acicular filler is used alone, it achieves the desired low gloss but tends to exacerbate stress whitening, while the use of polysilsesquioxane (PSQ) solid particles alone does not achieve the desired low gloss, but even adding a small amount of PSQ particles to the polycarbonate with reduced amounts of acicular fillers achieves the desired low gloss and stress whitening becomes acceptable while maintaining other desired mechanical properties.

[0044] The total loading of PSQ particles and needle-shaped fillers is generally about 5% to 20% by weight of the composition. Preferably, the amount is at least about 6% or 7.5% to a maximum of about 17.5%, 15% or even 13%. The ratio of needle-shaped fillers / polysilsesquioxane solid particles can vary over a wide range, such as 10 to 0.1 or 5 to 0.5. In one embodiment, the ratio is ideally greater than about 1 to achieve certain desired mechanical properties for certain applications, but this should not be interpreted in any non-limiting manner.

[0045] Preferably, the needle-shaped filler has a needle-shaped morphology, wherein the aspect ratio is at least 2 to 50, wherein needle-shaped in this article means that the morphology can be needle-shaped or plate-shaped, but preferably needle-shaped. Needle-shaped means that there are two smaller equivalent dimensions (commonly referred to as height and width) and a larger dimension (commonly referred to as length). Plate-shaped means that there are two larger dimensions (usually width and length) that are equivalent to a certain extent and a smaller dimension (usually height). More preferably, the aspect ratio is at least 3,4 or 5 to 25,20 or 15. The average aspect ratio is determined by measuring the longest and shortest dimensions of a random representative particle sample (e.g., 100 to 200 particles) by microphotography. The particle size of the needle-shaped filler needs to be a useful size, neither too large (e.g., across the minimum size of the desired product) nor too small to achieve the desired effect on mechanical properties. When defining a useful size, particle size and size distribution are given by median size (D50), D10, D90 and maximum size limits. This size is the equivalent spherical diameter by volume measured by laser scattering (Rayleigh or Mie, preferably Mie scattering) using a dispersion of solids in a liquid at a low solids loading. By volume, D10 is the size at which 10% of the particles have a smaller size, D50 (median) is the size at which 50% of the particles have a smaller size, and D90 is the size at which 90% of the particles have a smaller size. Typically, the filler has an equivalent spherical diameter median (D50) particle size of 0.1 micron to 25 microns, D10 of 0.05 to 5 microns, D90 of 20 to 40 microns, and essentially no particles greater than about 70 microns or even 50 microns, and no particles less than about 0.01 microns. Ideally, the median is 5 to 10 microns, D10 of 0.5 to 2 microns, and D90 of 20 to 30 microns.

[0046] Needle-shaped fillers, because they are not spherical and may have different aspect ratios, may have a greater impact on the processability of polycarbonate because the excess surface area is not directly related to the size determined by light scattering methods. Therefore, the specific surface area of ​​the needle-shaped filler should ideally be 0.1 m 2 / g to 20m 2 / g, preferably 2m 2 / g to 10m 2 / g. Likewise, to achieve improved compatibility with polycarbonate, the needle-shaped filler desirably has an amount of base that does not exceed about 0.5% by weight of the needle-shaped filler. Preferably, the amount of base does not exceed about 0.25% by weight.

[0047] In the composition of the present invention, it is critical that the polysilsesquioxane solid particles remain solid particles when processed into articles to achieve the desired stress whitening improvement while still achieving the necessary or desired mechanical properties. Since the melt processing of polycarbonate is dependent on the specific polycarbonate or polycarbonate copolymer, typically about 200°C to 300°C, the PSQ particles need to have a decomposition temperature above this temperature. Typically, the decomposition temperature of the PSQ particles is at least about 350°C or 400°C, preferably at least 500°C, 600°C or even 800°C or higher.

[0048] In addition, it is not understood but equally important that the PSQ particles should be spherical or nearly spherical, which may be related to how the needle-shaped filler and the PSQ particles interact in the polycarbonate article formed from the composition. Spherical or nearly spherical in this article refers to particles having an average projected sphericity (abbreviated as "sphericity") of at least 0.9 to 1. Preferably, the average sphericity is at least 0.95 or even 0.98. The average sphericity is calculated using the formula based on (4*A) / (π*L 2 ) measured on a randomly representative sample (e.g., 100 to 200 particles) from a micrograph, where A and L are the area and major diameter (maximum thickness) of the particle projection as obtained using image analysis as described in The Image Processing Handbook, Sixth Edition, JC Russ, CRC Press, 2011 (Chapter 11) and commercially available equipment and software readily available from suppliers such as Horiba Ltd.

[0049] The polysilsesquioxane herein refers to a polysilsesquioxane comprising a silsesquioxane monomer residue to achieve the desired PSQ solid particles. Silsesquioxane is a polysilsesquioxane of the formula R(SiO 3 / 2 ) n Siloxane wherein n is an even number greater than or equal to 4, such as 4, 6, 8, etc., and R is a phenyl group, a C1-C8 alkyl group, a cycloalkyl group, a C1-C8 olefin group, or any combination thereof. Silsesquioxane is a cage-like hybrid molecule of silicon and oxygen, similar to silicon dioxide and silicone. Si0 3 / 2 The units are assembled into spherical, highly symmetrical cage compounds. The terminal R units are not incorporated into the silicate backbone. These structural features lead to the name spherical siloxanes. There is a wide variety of spherical siloxanes in the silsesquioxanes. Many different terminal substituents (organic and inorganic, e.g., R = alkyl, aryl, hydroxyl, chlorine) are known. For n in the range of about 4 to about 18, Si0 3 / 2 The unit can be synthesized close to and represented by the following formula 6.

[0050]

[0051] wherein R is independently the same or different at each occurrence and is a hydrocarbon group such as phenyl, C1-C8 alkyl, cycloalkyl, C1-C8 olefin, or any combination thereof. Preferably, R is phenyl, methyl, ethyl, or vinyl, or a combination thereof. The polysilsesquioxanes either have a molecular weight or are cross-linked or form a three-dimensional structure, thereby exhibiting the above-mentioned properties. Suitable PSQ particles are available from several suppliers, such as Momentive Performance Materials Inc., Albany, NY, Shin-etsu Chemical Co., Ltd. Japan, commonly referred to as polymethylsilsesquioxanes. Particularly preferred PSQ particles are available from Shin-etsu under the name SR0326.

[0052] The PSQ particles have a size of the same order of magnitude as the median particle size of the needle-shaped filler measured by the same light scattering method or impedance change measurement method (such as Coulter CounterMultisizer II), but ideally have a narrower distribution. Even if one PSQ particle can be used, more than one PSQ particle with different sizes and distributions can be used, for example, with a bimodal or multimodal distribution of PSQ particles. Typically, the median particle (D50) size is between 0.1 and 20 microns by volume, preferably between 0.5 and 15 microns, and more preferably between 1 and 10 microns. To reiterate, the distribution of PSQ particles is ideally narrow unless intentionally widened by mixing two or more PSQ particles of different median sizes. Typically, by volume, D10 and D90 are within 50% of the D50 size, preferably within 30% of the D50, and there are essentially no particles greater than 100% D50 (illustratively, PSQ particles with a D50 of 5 microns will have no particles greater than 10 microns).

[0053] The composition can be used to form articles, and in a particular embodiment, the needle-shaped filler comprises calcium. When implementing the method, a composition is provided and the composition is heated to a temperature sufficient to melt the polycarbonate or copolycarbonate but not sufficient to decompose the PSQ particles. The processing temperature depends on the specific polycarbonate or copolycarbonate used, but generally the processing temperature will be between 200°C and 300°C or 350°C, sufficient to melt the polycarbonate. The heating is carried out in any suitable device, such as equipment known in the art, such as in situ in a screw extruder. The forming of the heated composition can be any known thermoplastic forming method, and includes, for example, extrusion, injection molding, film formation, hot pressing, and hot rolling. In one embodiment, a laminated structure is formed in which the composition of the present invention encapsulates or covers one side of a core plastic such as polycarbonate in the absence of needle-shaped fillers or PSQ particles (e.g., unfilled polycarbonate). Such articles can be made, for example, by a coextrusion process.

[0054] In the method of the present invention, the PSQ particles ideally maintain the same shape and size as the PSQ particles before being heated and formed into an article. That is, the particles have substantially the same particle size, particle size distribution, and sphericity within statistical errors caused by, for example, measurement techniques, sampling errors, etc. Typically, the PSQ particles after heating and forming will have the same shape and size as the PSQ particles before heating and forming, within an error of 10%. That is, the particles will not react or dissolve to the extent that they are incorporated into the polycarbonate polymer (e.g., intertwined with polycarbonate chains), and they will not deform under heating so that the sphericity drops below 0.9.

[0055] The article formed by this method typically has a gloss of 20 or less measured at 60° incident angle according to ISO 2813, wherein the article is made using a mirror polished tool. Mirror polish refers to a flat surface of sufficient area measured at 60° incident angle according to ISO 2813, wherein the surface roughness is at most about 0.10 microns Ra and 0.13 RMS roughness. Preferably, the gloss is at most 18, 15 or 12 to 1. The article ideally has PSQ particles and a filler comprising calcium, wherein the filler is acicular as previously described.

[0056] In one embodiment, the article comprises a polycarbonate or a polycarbonate copolymer in which are dispersed needle-shaped fillers having an aspect ratio of at least 2 to 50 and polysilsesquioxane solid particles having a sphericity of at least 0.9 as measured by the Pentland method. In this embodiment, the needle-shaped filler preferably comprises calcium, such as calcium silicate, calcium aluminate, or a combination thereof. The needle-shaped fillers and PSQ particles are ideally uniformly dispersed throughout the article. Uniformly means that in any 10 randomly selected cross-sections of the article, the amount of filler or PSQ particles is within 10% of the concentration in any one cross-section. The amount of filler can be determined by known microscopic techniques that evaluate, for example, the area of ​​the polished portion. Preferably, the sphericity of the PSQ particles is as described above, and the aspect ratio of the needle-shaped filler is also as described above for the composition.

[0057] The articles of the present invention can be used in applications requiring an opaque aesthetic and being subjected to flexure such as bending. Illustrative examples include, but are not limited to, luggage, containers, white parts of automobile bodies, and the like.

[0058] Illustrative Embodiments

[0059] The following embodiments are provided to illustrate the present invention, but are not intended to otherwise limit the scope of the present invention. The present invention encompasses and contemplates any and all combinations of the following embodiments, including those contained in the claims.

[0060] 1. A thermoplastic composition comprising a polycarbonate or a polycarbonate copolymer; and at least 1% by weight of solid particles of a polysilsesquioxane having a decomposition temperature of at least 350°C and a needle-shaped filler.

[0061] 2. The composition according to aspect 1, wherein the filler is calcium silicate, calcium aluminosilicate or a mixture thereof.

[0062] 3. The composition of aspect 1 or 2, wherein the needle-shaped filler has a median equivalent spherical diameter of 0.1 micrometer to 25 micrometers, and is substantially free of particles larger than 70 micrometers.

[0063] 4. The composition of any one of the preceding aspects, wherein the needle-shaped filler has an aspect ratio of at least 2 to 50.

[0064] 5. The composition of any one of the preceding aspects, wherein the acicular filler has an aspect ratio of at least 5 to 25.

[0065] 6. A composition as described in any of the preceding aspects, wherein the needle-shaped filler has at least 0.1 m 2 / g to 20m 2 / g specific surface area.

[0066] 7. A composition as described in any one of the preceding aspects, wherein the needle-shaped filler has at least 2 m 2 / g to 10m 2 / g specific surface area.

[0067] 8. The composition of any one of the preceding aspects, wherein the needle-shaped filler has an amount of Mg and alkali of less than 0.5 wt%.

[0068] 9. The composition of aspect 8, wherein the amount of Mg and alkali is less than 0.25 wt%.

[0069] 10. The composition of any of the preceding aspects, wherein the polysilsesquioxane solid particles and acicular filler are present in the composition in an amount of 5% to 20% by weight of the composition.

[0070] 11. The composition of aspect 10, wherein the amount is 7.5% to 15% by weight of the composition.

[0071] 12. The composition according to any one of the preceding aspects, wherein the needle-shaped filler and the polysilsesquioxane solid particles are present in the composition in a filler / polysilsesquioxane solid particle mass ratio of 10 to 0.1.

[0072] 13. The composition of aspect 12, wherein the mass ratio is 5 to 0.5.

[0073] 14. The composition of any of the preceding aspects, wherein the polysilsesquioxane solid particles have a decomposition temperature of at least 400°C.

[0074] 15. The composition of any one of the preceding aspects, wherein the polysilsesquioxane is cross-linked or has a 3D structure.

[0075] 16. A composition as described in any of the preceding aspects, wherein the polysilsesquioxane is formed from silsesquioxane, the silsesquioxane being of the formula R(SiO 3 / 2 )n siloxane, wherein n is equal to an even number greater than or equal to 4 to 16, and R at each occurrence is independently aryl, C1 to C8 alkyl, cycloalkyl, vinyl, or a combination thereof.

[0076] 17. The composition of aspect 16, wherein R is phenyl, methyl, ethyl, vinyl, or a combination thereof.

[0077] 18. The composition of aspect 17, wherein R is phenyl, methyl, vinyl, or a combination thereof.

[0078] 19. The composition of any of the preceding aspects, wherein the composition further comprises a stabilizing salt.

[0079] 20. The composition of aspect 15, wherein the stabilizing salt is present in an amount of 0.05 to about 0.5 weight percent of the composition.

[0080] 21. The composition of aspect 19 or 20, wherein the stabilizing salt is a phosphorus-based acid.

[0081] 22. The composition of aspect 15, wherein the stabilizing salt is monosodium phosphate.

[0082] 23. The composition of any of the preceding aspects, further comprising one or more of an antioxidant, a colorant, a dye, an anti-drip agent, and an impact modifier.

[0083] 24. The composition of aspect 23, wherein the antioxidant is present in an amount of about 200 parts per million to about 2000 parts per million by weight of the composition.

[0084] 25. The composition of any of the preceding aspects, wherein the polycarbonate or polycarbonate copolymer is branched, linear, or a mixture of branched and linear polycarbonates.

[0085] 26. The composition of any of the preceding aspects, wherein the polycarbonate or polycarbonate copolymer is an aromatic polycarbonate.

[0086] 27. The composition of any of the preceding aspects, wherein the polysilsesquioxane solid particles have an average sphericity of at least 0.9 as measured by image analysis of projections of the particles in micrographs.

[0087] 28. The composition of aspect 27, wherein the average sphericity is at least 0.95.

[0088] 29. The composition of any of the preceding aspects, wherein the polysilsesquioxane solid particles have a volume median particle size of 1 to 20 microns, with substantially no particles greater than 70 microns.

[0089] 30. The composition of aspect 29, wherein the median particle size is 1 to 10 microns by volume, and there are substantially no particles greater than 20 microns by volume.

[0090] 31. The composition of aspect 30, wherein substantially all of the particles have a size within ±50% of the median.

[0091] 32. An article comprising the composition of any of the preceding aspects.

[0092] 33. The article of aspect 32, wherein the article has a top or bottom gloss of 20 or less measured according to ISO 2813 at an incident angle of 60°.

[0093] 34. The article of aspect 33, wherein the top or bottom gloss is 12 or less.

[0094] 35. A method of forming an article comprising

[0095] (i) providing a composition comprising polycarbonate or a polycarbonate copolymer and at least 1% by weight of solid particles of a polysilsesquioxane having a decomposition temperature of at least 350° C. and a needle-shaped filler,

[0096] (ii) heating the composition of step (i) to a temperature sufficient to melt the polycarbonate or polycarbonate copolymer but insufficient to decompose the polysilsesquioxane solid particles, and

[0097] (iii) shaping the heated composition to form an article having the polysilsesquioxane solid particles and acicular filler dispersed therein.

[0098] 36. The method of clause 35, wherein the polysilsesquioxane solid particles are not deformed or incorporated into the polycarbonate.

[0099] 37. The method of aspects 35 or 36, wherein the polysilsesquioxane solid particles have an average sphericity of at least 0.9 within the article.

[0100] 38. The method of any one of aspects 31 to 37, wherein the polysilsesquioxane solid particles and acicular fillers are uniformly dispersed in the article.

[0101] 39. An article comprising polycarbonate or a polycarbonate copolymer having dispersed therein solid particles of a filler having an aspect ratio of at least 2 to 50 and polysilsesquioxane having an average sphericity of at least 0.9.

[0102] 40. The article of aspect 39, wherein the acicular filler is calcium silicate, calcium aluminosilicate, or a combination thereof.

[0103] 41. The article of aspect 39 or 40, wherein the filler and the polysilsesquioxane solid particles are present in the composition in a filler / polysilsesquioxane solid particle mass ratio of 10 to 0.1.

[0104] 42. The article of any one of aspects 39 to 40, wherein the acicular filler is wollastonite.

[0105] 43. The method of any one of aspects 35 to 38, wherein the acicular filler is wollastonite.

[0106] 44. The composition of any one of aspects 1 to 31, wherein the acicular filler is wollastonite.

[0107] Example

[0108] The following examples are provided to illustrate the present invention but are not intended to limit its scope. Unless otherwise indicated, all parts and percentages are by weight.

[0109] In forming the examples, two batches were melt blended and molded to form samples for mechanical testing and stress whitening evaluation. In the first batch (Batch 1), polycarbonate (NYGLOS 4W 10992, available from Imerys Performance Additives, San Jose, CA) containing wollastonite particles was melt blended, having the formulation shown in Table 1. The D50 was about 2 microns, and the sphericity was greater than 0.9. This batch had a light purple hue from the purple dye, which aided in the stress whitening evaluation.

[0110] The second batch (Batch 2) of polycarbonate contained PSQ particles (Shinetsu SR0326, available from Shinetsu Chemical Co., Ltd., Japan) and had the formulation shown in Table 2. Batch 2 had a light brown color due to the presence of wollastonite. The aspect ratio of wollastonite was about 9. D50 was about 6.5.

[0111] The formulations used to prepare the comparative examples and examples are shown in Table 3. Comparative Example 1 is a neat polycarbonate PC-200 available from Trinseo SA under the trade name CALIBER PC-200. Gloss was measured using ISO 2813 using a 60° angle of incidence on 3 mm thick plaques. The average gloss of one surface is reported, where 5 measurements were made on different plaques to give the average gloss. The plaques were made by injection molding in a mirror polished tool at a melt temperature of 270°C and a tool temperature of 100°C. The injection speed was 35 mm / minute and the cooling time was 25 seconds. Two millimeter thick dart impact plaques were prepared using the same conditions just described. Dart impact was determined using ISO 6603-2.

[0112] Elongation at break, elongation at yield, tensile modulus, yield stress and stress at break were measured on tensile specimens using ISO 527. The tensile specimens were made by injection molding at a melt temperature of 320° C. and a tool temperature of 100° C. The injection speed was 35 mm / min and the cooling time was 25 seconds.

[0113] The notched charpy test was carried out at a temperature of 23° C. according to ISO 179. The Charpy test specimens were made by injection molding at a melt temperature of 320° C. and a tool temperature of 100° C. The injection speed was 35 mm / min and the cooling time was 25 seconds.

[0114] From the data corresponding to Comparative Example 1 and Example 2 and Figure 1A and 1B It is evident that stress whitening is significantly improved while retaining the desired low gloss (matte) finish without any significant loss of desired mechanical properties. Figure 2 and 3 The microstructure of Example 2 is shown, where it is apparent that the PSQ particles retain their spherical or rounded shape, and both the PSQ particles and the needle-shaped particles are uniformly distributed within the article.

[0115] Table 1

[0116]

[0117] Table 2

[0118]

[0119] MFR = Melt Flow Rate (g / 10 min) Table 3

[0120]

[0121] Table 4

[0122]

[0123] FDI = Falling Dart Impact

Claims

1. A thermoplastic composition comprising a polycarbonate or a polycarbonate copolymer; and at least 1 wt % of polysilsesquioxane solid particles and a needle-like filler; wherein the needle-like filler and the polysilsesquioxane solid particles are present in the composition at a mass ratio of needle-like filler / polysilsesquioxane solid particles of 10 to 0.1; wherein the needle-like filler has a median particle size (D50) of 0.1 to 25 microns, and the polysilsesquioxane solid particles have a median particle size (D50) of 0.1 to 20 microns, and wherein the polysilsesquioxane is cross-linked or has a 3D structure.

2. The composition of claim 1, wherein the filler comprises calcium.

3. The composition of claim 1 or 2, wherein the needle-shaped filler has an aspect ratio of 2 to 50.

4. The composition of claim 1 or 2, wherein the polysilsesquioxane solid particles and the acicular filler are present in the composition in an amount of 5 to 20 wt% of the composition. 5 . The composition according to claim 1 , wherein the needle-shaped filler and the polysilsesquioxane solid particles are present in the composition at a filler / polysilsesquioxane solid particle mass ratio of 5 to 0.

1.

6. The composition of claim 1 or 2, wherein the polysilsesquioxane is formed from silsesquioxane, the silsesquioxane being of the formula R(SiO 3 / 2 )n siloxane, wherein n is equal to an even number greater than or equal to 4 to 16, and R at each occurrence is independently aryl, C1 to C8 alkyl, cycloalkyl, vinyl, or a combination thereof.

7. The composition according to claim 1 or 2, wherein The polysilsesquioxane solid particles have an average sphericity of at least 0.9 as measured by image analysis of projections of the particles in micrographs.

8. An article comprising the composition of any one of claims 1 to 7.

9. The article of claim 8, wherein the article has a gloss of 20 or less, as measured according to ISO 2813 at a 60° incident angle from a sample prepared using a mirror polished tool.

10. A method of forming an article, comprising (i) providing a composition comprising a polycarbonate or a polycarbonate copolymer and at least 1 wt % of a polysilsesquioxane solid particle having a decomposition temperature of at least 350° C. and a needle-shaped filler; wherein the needle-shaped filler and the polysilsesquioxane solid particle are present in the composition at a mass ratio of needle-shaped filler / polysilsesquioxane solid particle of 10 to 0.1; wherein the needle-shaped filler has a median particle size (D50) of 0.1 μm to 25 μm, and the polysilsesquioxane solid particle has a median particle size (D50) of 0.1 μm to 20 μm, and wherein the polysilsesquioxane is cross-linked or has a 3D structure, (ii) heating the composition of step (i) to a temperature sufficient to melt the polycarbonate or polycarbonate copolymer but insufficient to decompose the polysilsesquioxane solid particles, and (iii) shaping the heated composition to form an article having the polysilsesquioxane solid particles and acicular filler dispersed therein.

11. The method of claim 10, wherein the polysilsesquioxane solid particles have an average sphericity of at least 0.9 within the article.

12. An article comprising a polycarbonate or a polycarbonate copolymer, wherein a needle-shaped filler having an aspect ratio of 2 to 50 and polysilsesquioxane solid particles having an average sphericity of at least 0.9 are dispersed, wherein the article has a gloss of 20 or less measured at an incident angle of 60° from a sample prepared using a mirror polished tool according to ISO 2813; wherein the needle-shaped filler has a median particle size (D50) of 0.1 micrometer to 25 micrometers, and the polysilsesquioxane solid particles have a median particle size (D50) of 0.1 micrometer to 20 micrometers, and wherein the polysilsesquioxane is cross-linked or has a 3D structure.

13. The article of claim 12, wherein the filler and the polysilsesquioxane solid particles are present in the article in a filler / polysilsesquioxane solid particle mass ratio of 10 to 0.1, and the filler comprises wollastonite.

Citation Information

Patent Citations

  • Flame-retardant, stress crack resistant polycarbonate ABS moulding composition

    EP0640655A2

  • Thermoplastic aromatic polycarbonates and their manufacture

    US3028365A

  • Organopolysiloxane polycarbonate block copolymers

    US3419634A

  • Filled thermoplastic resin compositions

    US4243575A

  • Deactivation of polyester catalyst residues

    US4401804A